2013
DOI: 10.5114/ninp.2013.34462
|View full text |Cite
|
Sign up to set email alerts
|

The β-fibrinogen –455G/A gene polymorphism and the risk of ischaemic stroke in a Polish population

Abstract: The β-fibrinogen -455G/A gene polymorphism is not a risk factor for ischaemic stroke in a Polish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…In a similar study in Poland, 426 ischemic stroke patients and 234 controls were examined. Genotype frequencies were GG 75%, GA 36.8%, AA 6.6% in patient group and GG 5.3%, GA 32.9% and AA 9.8% in control group, and no significant difference was found between the patient and control groups in terms of this mutation [44]. GA genotype frequency, which is 33.3% in our patient group, is similar to the genotype frequency in the study conducted in Poland.…”
Section: β-Fibrinojen -455g > a Mutationsupporting
confidence: 82%
“…In a similar study in Poland, 426 ischemic stroke patients and 234 controls were examined. Genotype frequencies were GG 75%, GA 36.8%, AA 6.6% in patient group and GG 5.3%, GA 32.9% and AA 9.8% in control group, and no significant difference was found between the patient and control groups in terms of this mutation [44]. GA genotype frequency, which is 33.3% in our patient group, is similar to the genotype frequency in the study conducted in Poland.…”
Section: β-Fibrinojen -455g > a Mutationsupporting
confidence: 82%
“…Moreover, it was found that -455 G/A was independently associated with an increased risk of CES in AF patients and the significance remained after the Bonferroni correction in the additive (AA vs. GA vs. GG), dominant (AA + GA vs. GG), and recessive models (AA vs. GA + GG), with ORs of 1.548 (95% CI: 1.251–1.915, p = 0.001), 1.588 (95% CI: (1.226–2.057, p = 0.003), and 2.394 (95% CI: 1.357–4.223, p = 0.015) [ 89 ]. In the study by Golenia et al, which included 426 Polish patients with ischemic stroke, it was shown that the β-fibrinogen -455 G/A gene polymorphism was not a risk factor for this disease [ 90 ]. Reviewing the results of other studies, one can find evidence of a different effect of the presence of the -455 G/A polymorphism on the risk of CAD (increased risk, no effect and protective effect) [ 91 , 92 , 93 ].…”
Section: Fibrinogen Molecular Modifications and Cardiovascular Riskmentioning
confidence: 99%
“…A positive association with hypertension and smoking was previously reported by Martiskainen et al (12) in lacunar stroke patients carriers of the FGB −455G>A A allele. In contrast, other studies (30,31) failed to find any association between the FGB −455G>A polymorphism and smoking or hypertension in patients with stroke. Following the available literature data on the association of GP IIIa PIA1/A2 polymorphism with hypertension and smoking, we found conflicting results.…”
Section: Discussionmentioning
confidence: 65%